2012
DOI: 10.1007/s00403-012-1299-0
|View full text |Cite
|
Sign up to set email alerts
|

c.1643_1644delTG XPC mutation is more frequent in Moroccan patients with xeroderma pigmentosum

Abstract: Xeroderma pigmentosum is a rare autosomal recessive disease characterized by hypersensitivity to UV light which is due to alterations of the nucleotide excision repair pathway. Eight genes (XPA to XPG and XPV) are responsible for the disease. Among them, the XPC gene is known to be the most mutated in Mediterranean patients. The aim of this study was to determine the frequency of the most common XPC mutation and describe the clinical features of Moroccan patients with xeroderma pigmentosum. Twenty four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Interestingly, Mahindra et al [ 41 ] also described the XPC mutation in two brother patients from North Sudan. Furthermore, the molecular analysis of 24 Moroccan patients showed that 17 were homozygous for the c.1643_1644delTG mutation [ 42 ]. Most XP-C African patients with delTG mutation in both alleles have similar clinical features consisting of photosensitivity, pigmentary lesions, and early onset of skin cancer without neurological involvement as our XP-C patients [ 22 , 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Mahindra et al [ 41 ] also described the XPC mutation in two brother patients from North Sudan. Furthermore, the molecular analysis of 24 Moroccan patients showed that 17 were homozygous for the c.1643_1644delTG mutation [ 42 ]. Most XP-C African patients with delTG mutation in both alleles have similar clinical features consisting of photosensitivity, pigmentary lesions, and early onset of skin cancer without neurological involvement as our XP-C patients [ 22 , 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by its high carriers frequency estimated to be 1/250 in Morocco [12]. Having a homogeneous mutational spectrum for the XPC gene has greatly simplified the molecular diagnosis of XP-C in the region [6, 8, 13]. Furthermore, two other private mutations have been recently reported in North African patients [6].…”
Section: Introductionmentioning
confidence: 97%
“…Molecular investigations of the XP-C group showed that it is the major group among the five North African countries called the Maghreb [6, 8, 12, 13]. Indeed, among the studied patients, about 87% of them shared the recurrent founder mutation c.1643_1644delTG (p.V548AlafsX25) [6].…”
Section: Introductionmentioning
confidence: 99%
“…13 The c.1643_1644delTG mutation in the XPC gene represents the major cause of xeroderma pigmentosum in Maghreb region (Morocco, Algeria and Tunisia); haplotype analysis revealed the presence of a common founder effect for this XPC mutation in the Mediterranean region. 14,15 The identification of founder mutations has important implications in molecular diagnosis and genetic counselling. Furthermore, a few prevalent founder mutations enable human geneticists to make more efficient genetic screening than testing for many rare mutations.…”
Section: Discussionmentioning
confidence: 99%